IMPLEMENTASI AUGMENTED REALITY PADA MEDIA PENGENALAN PRODI SISTEM INFORMASI FST UINSU MEDAN - Mohammad Badri; Ali Ikhwan; Raissa Amanda Putri (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2022)
One of the study programs at the Faculty of Science and Technology (FST) UIN North Sumatra Medan is the Information Systems Study Program. During the Introduction to Academic and Student Culture (PBAK) or what is usually called the orientation period, the introduction of the campus environment in the form of facilities, buildings and rooms is not very clear because it only uses video either during live or online introductions like the current pandemic, so new students do not can find out in detail. Augmented Reality (AR) applications can be a solution to make recognition clearer than video. The method in the AR application used is Markerless Augmented Reality (User Defined Target). This application was built using the C# programming language and the Rapid Application Development development method. The purpose of research and making this application is to make it easier for users (new students) to get information about the campus environment. Users can easily view the existing facilities in the Information Systems Study Program, the layout of the IV UINSU Medan campus building and the FST UINSU Medan room plan directly from their smartphone anywhere and anytime without having to ask the officers around the campus. The information presented in this application is good, easy and smooth to use and testing gets good results.